Meningkatan Hasil Belajar Peserta Didik Pada Pembelajaran Tematik Terpadu dengan Model CIRC di Kelas V Sekolah Dasar - Ati, Murni; Mansurdin, Mansurdin (Universitas Negeri Padang, 2023)
This study aims to describe the improvement of students' learning outcomes in integrated learning using the Cooperative Integrated Reading and Composition (CIRC) model in Elementary School. This type of research was a classroom action research (PTK) which takes place in two rounds, round I with 2 meetings, and round II with 1 meeting. Each phase consists of planning, implementation, observation, and reflection. The subjects are teachers and students of grade five and a total of 22 people. The research approaches used are qualitative and quantitative with data collection in the form of observation, testing and non-testing. The results cycle I under the part of the lesson plan received an average of 80.5% with good qualifications and cycle II an average of 94.44% with very good. The implementation of learning in cycle I of the teacher's part got an average of 82.81% with good qualification and cycle II an average of 96.87% with qualification (A), in cycle I students average 82.81% with a good qualification in cycle II an average of 96.87% has a very good qualification. Evaluation in cycle I of the academic achievement of students gets an average of 79.25 (C) and in cycle II an average of 91.5 (A). Based on these findings, it can be concluded that the CIRC model can improve integrated learning outcomes in elementary schools.